2020
DOI: 10.1111/exd.14070
|View full text |Cite
|
Sign up to set email alerts
|

Immune cell regulation of the hair cycle

Abstract: The ability to manipulate the mammalian hair cycle will lead to novel therapies and strategies to combat all forms of alopecia. Thus, in addition to the epithelial‐mesenchymal interactions in the hair follicle, niche and microenvironmental signals that accompany the phases of growth, regression and rest need to be scrutinized. Immune cells are well described in skin homeostasis and wound healing and have recently been shown to play an important role in the mammalian hair cycle. In this review, we will summariz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 145 publications
(212 reference statements)
1
30
0
Order By: Relevance
“…[ 85 ] Another notable observation is that CRH stimulates mast cell maturation and degranulation in the human HF connective tissue sheath [ 86 ] , which is required for initiation of the hair regression phase. [ 87 ] Of note, perifollicular microinflammation which is characterized by an invasion of immune cells (T cells, macrophages) and mast cell degranulation has been observed in scalp regions with actively progressing alopecia. [ 10 ] In terms of the observed effects of CRH on hair growth, genetic variants affecting CRHR1 signalling could thus contribute to the characteristic premature catagen entry and the gradual transformation of pigmented terminal into unpigmented vellus hair that are observed in AGA.…”
Section: Corticotropin‐ and Gonadotropin‐releasing Hormone Signallingmentioning
confidence: 99%
“…[ 85 ] Another notable observation is that CRH stimulates mast cell maturation and degranulation in the human HF connective tissue sheath [ 86 ] , which is required for initiation of the hair regression phase. [ 87 ] Of note, perifollicular microinflammation which is characterized by an invasion of immune cells (T cells, macrophages) and mast cell degranulation has been observed in scalp regions with actively progressing alopecia. [ 10 ] In terms of the observed effects of CRH on hair growth, genetic variants affecting CRHR1 signalling could thus contribute to the characteristic premature catagen entry and the gradual transformation of pigmented terminal into unpigmented vellus hair that are observed in AGA.…”
Section: Corticotropin‐ and Gonadotropin‐releasing Hormone Signallingmentioning
confidence: 99%
“…Immune cell dynamics is associated with the transition of HF through the cycle and, in some degree, provides regulatory keys for it. We will discuss some striking features of this interconnection (for review see: Wang and Higgins, 2020) along with specific stage characteristics.…”
Section: The Hf Cycle and Immunity In Physiological And Injury-inducementioning
confidence: 99%
“…Catagen is induced by growth factors and cytokines, including FGF5 secreted by perifollicular macrophages and IFN-γ (Wang and Higgins, 2020). Fgf5 mutations cause catagen retention in humans (Higgins et al, 2014).…”
Section: The Hf Cycle and Immunity In Physiological And Injury-inducementioning
confidence: 99%
“…Wang and Higgins review the evidence to date and consider the mechanisms of immune cell influence over hair growth and hair loss. [34] Perifollicular mast cells, γδ T cells, natural killer cells and macrophages are understood to affect hair growth cycles via secretion of hair follicle-targeting growth factors. [35] Interestingly, recent studies suggest another mode of action by which cells may signal to each other.…”
Section: Hair B I Ologymentioning
confidence: 99%
“…Inflammation has long been recognized as a primary driver of non‐scarring and scarring alopecias, but more recently, research studies have shown that cells of the innate and adaptive immune systems may also play a role in regulating and modifying the normal hair cycle. Wang and Higgins review the evidence to date and consider the mechanisms of immune cell influence over hair growth and hair loss . Perifollicular mast cells, γδ T cells, natural killer cells and macrophages are understood to affect hair growth cycles via secretion of hair follicle‐targeting growth factors .…”
Section: Hair Biologymentioning
confidence: 99%